2002
DOI: 10.1016/s0014-5793(02)03100-9
|View full text |Cite
|
Sign up to set email alerts
|

Supramolecular organization of photosystem I and light‐harvesting complex I in Chlamydomonas reinhardtii

Abstract: We report a structural characterization by electron microscopy and image analysis of a supramolecular complex consisting of photosystem I and light-harvesting complex I from the unicellular green alga Chlamydomonas reinhardtii. The complex is a monomer, has longest dimensions of 21.3 and 18.2 nm in projection, and is signi¢cantly larger than the corresponding complex in spinach. Comparison with photosystem I complexes from other organisms suggests that the complex contains about 14 light-harvesting proteins, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

17
111
0
3

Year Published

2003
2003
2013
2013

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 104 publications
(131 citation statements)
references
References 29 publications
17
111
0
3
Order By: Relevance
“…The alignment with D. salina complexes revealed that the PS-I antenna in iron-sufficient cells is significantly larger than that of pea. These results are in agreement with the comparison of PS-I-LHC-I complexes from C. reinhardtii and from spinach by single particle analysis (34,36). The antenna of iron-deficient PS-I is even larger and further extends on the opposite side of the RC.…”
Section: Imaging Of the Ps-i-lhc-i By Single Particle Electronsupporting
confidence: 90%
See 1 more Smart Citation
“…The alignment with D. salina complexes revealed that the PS-I antenna in iron-sufficient cells is significantly larger than that of pea. These results are in agreement with the comparison of PS-I-LHC-I complexes from C. reinhardtii and from spinach by single particle analysis (34,36). The antenna of iron-deficient PS-I is even larger and further extends on the opposite side of the RC.…”
Section: Imaging Of the Ps-i-lhc-i By Single Particle Electronsupporting
confidence: 90%
“…The diameter of the complexes was estimated to be 22, 31, and 37 nm for complex 3, ⑀, and ␣, respectively. The shape and dimensions of complex 3 from control D. salina cell are similar to reported dimensions for PS-I-LHC-I complexes from C. reinhardtii (21.3 ϫ 18.2 nm) (34).…”
Section: Imaging Of the Ps-i-lhc-i By Single Particle Electronsupporting
confidence: 78%
“…PSI-LHCI complexes were obtained from C. reinhardtii strain CC-2137 by -DM solubilization and sucrose gradient centrifugation as described in Germano et al 33 with an additional FPLC run through a Superdex 200 column after the ultracentrifugation. This preparation was characterized before by electron microscopy 33 and consists of two slightly different types of particles which however contain the same number of LHCI subunits. 34 These types of complexes bind most likely 9 LHCI subunits per PSI core complex 35 and contain about 230 Chls (M. Hippler, personal communication; ref 26).…”
Section: Methodsmentioning
confidence: 99%
“…Thus, when the three mobile LHCII proteins are bound to PSI, the possible binding site could be modeled near the PsaH subunit. Germano et al (34) postulated that a mass of 40 nm 2 near this region in one of their single-particle images of PSI-LHCI supercomplex from C. reinhardtii corresponds to three LHCI monomers. It is possible that the three monomeric LHCII proteins identified in this study occupy the same region.…”
Section: Figmentioning
confidence: 99%
“…It is possible that the three monomeric LHCII proteins identified in this study occupy the same region. The PSI-LHCI supercomplex is much larger in C. reinhardtii than in higher plants (34,35) perhaps because the alga has nine Lhca genes (Fig. 5), whereas higher plants have only four or five.…”
Section: Figmentioning
confidence: 99%